Synthesis and cytotoxicity of novel 14α-O-(andrographolide-3-subsitutedisoxazole-5-carboxylate) derivatives. Issue 21 (2nd November 2021) - Mokenapelli, Sudhakar; Yerrabelli, Jayaprakash Rao; Das, Neeladrisingha; Roy, Partha; Chitneni, Prasad Rao
Abstract: Simple and efficient method was established for the synthesis of a new family of 14α- O -(andrographolide-3-subsitutedisoxazole-5-carboxylate) derivatives (10a-j ) from naturally occurring andrographolide (1 ) by selective esterification with propiolic acid at C-14 using protection and deprotection strategy followed by metal free 1, 3-dipolar cycloaddition with aryl nitrile oxides. All the synthesised derivatives were tested for their cytotoxicity against HCT-15, HeLa and DU145 cell lines. Most of the compounds exhibited improved cytotoxic activity compared to the parent molecule andrographolide (1 ), as the compounds 10b, 10c, 10i, 10j, 11d and 11f showed significant cytotoxicity against three cancer cell lines. Except the compound 10b and 11d, all the compounds did not inhibit the normal cell line (VERO). Based on these studies isoxazole ester derivatives at C-14 of andrographolide with various substitutions promoting anticancer activities and better safety profiles. Further studies in this direction with improved water solubility and oral bioavailability are in progress in future. Graphical Abstract: